TINGKAT PEMAHAMAN PERATURAN PERMAINAN SEPAK BOLA (LAW OF THE GAME) WASIT C3 ASKAB PSSI ACEH BESAR - khairul hakiki; Erizal Kurniawan; Musran (CV Abid Abadi Jaya, 2026)
The purpose of this study was to determine the level of understanding of football rules (Laws of the Game) referee C3 ASKAB PSSI Aceh Besar. This research uses a qualitative approach with descriptive type. The population of this study was the referee C3 ASKAB PSSI Aceh Besar, and the sample was 18 people with total sampling technique. Data collection in this study using a questionnaire with Guttman scale measurements. Data analysis using percentage analysis. The results showed that the majority of referees, namely 84.21% or as many as 16 people, have a moderate level of understanding, while 15.78% or 3 people who are classified in the high understanding category. This finding confirms the need to increase the competence of referees through various programmes such as training, coaching and skill development in order to improve the quality of refereeing. The research concluded that the level of understanding of football rules (Laws of the Game) of referee C3 ASKAB PSSI Aceh Besar is in the medium category